The methodology of Al-Kissa'i in selecting the Qira’at of the Qur'an: An applied theoretical study - Meddah, Aboubakr; Aouad, Hamza (Journal of Human Sciences, 2025)
The topic of this article deals with Al-Kissa'i's methodology in selecting the qira'at. The research begins with an introduction to introduce the topic, then a preface on selection in the qira'at, then a biography of Imam Al-Kissa'i, then a study of the criteria for providing evidence for the qira'at according to him, then a conclusion containing the most important findings. The research confirmed that Al-Kissa'i's approach in choosing the qira'at was characterised by following what is stipulated, and That most of his choices are in accordance with the qira'at of the people of Kufa, which is the qira'at of his sheikhs, except in some places he disagreed with their qira'at and chose the qira'at of the people of Hijaz or Basrah, and that the most prominent criteria he adopted in selecting the qira'at: Approval of the explicit Quranic script, approval of the qira'at of the Prophet _peace be upon him_ or the qira'at of the Companions, consideration of the intervals between verses, and consideration of the most clear meaning.